A systematic review of English medium instruction in higher education. (12th December 2017) - Macaro, Ernesto; Curle, Samantha; Pun, Jack; An, Jiangshan; Dearden, Julie
Abstract : After outlining why a systematic review of research in English medium instruction (EMI) in higher education (HE) is urgently required, we briefly situate the rapidly growing EMI phenomenon in the broader field of research in which content and language have been considered and compare HE research outputs with those from other phases of education. An in-depth review of 83 studies in HE documents the growth of EMI in different geographical areas. We describe studies which have investigated university teachers' beliefs and those of students before attempting to synthesise the evidence on whether teaching academic subjects through the medium of English as a second language (L2) is of benefit to developing English proficiency without a detrimental effect on content learning. We conclude that key stakeholders have serious concerns regarding the introduction and implementation of EMI despite sometimes recognising its inevitability. We also conclude that the research evidence to date is insufficient to assert that EMI benefits language learning nor that it is clearly detrimental to content learning. There are also insufficient studies demonstrating, through the classroom discourse, the kind of practice which may lead to beneficial outcomes. This insufficiency, we argue, is partly due to research methodology problems both at the micro and macro level.